A techno-economic comparison of traditional upgrades, volt-var controls, and coordinated distributed energy resource management systems for integration of distributed photovoltaic resources. (December 2020) - Horowitz, Kelsey A.W.; Jain, Akshay; Ding, Fei; Mather, Barry; Palmintier, Bryan
Highlights: Cost and performance of three options for expanding PV hosting capacity are compared. Volt-var controls avoid upfront costs but do not expand the hosting capacity as much. DERMS results in the largest hosting capacity increase. PV curtailment is higher with DERMS than volt-var control. Abstract: In some cases, increased deployment of distributed photovoltaic (PV) systems can impact the distribution grid, including causing steady-state voltages and thermal loading of lines and equipment to deviate from operational limits. We present techno-economic analysis of three possible solutions for mitigating these effects on two real feeders: traditional infrastructure upgrades, autonomous volt-var controls, and a distributed energy management system (DERMS). We focus on issues arising in aggregate from residential and small commercial PV systems at different penetration levels and use a bottom-up approach that couples cost modeling with sequential hosting capacity analysis and quasi-static time-series simulation. We compare trade-offs for each solution in terms of effectiveness, upfront capital costs, operating costs, PV output curtailment, and distribution system losses. We find that volt-var controls offer the lowest cost option for hosting capacity expansion but cannot mitigate all violations at high penetration levels. For the feeders studied, the range of upfront cost for the DERMS and traditional upgrades is similar, but the DERMS results in a greater expansion of the hosting capacity. However, unlike traditional solutions, DERMS also involves higher level of PV curtailment than is observed with autonomous volt-var controls.